Patient and caregiver perspectives on care coordination during transitions of surgical care. Issue 3 (23rd May 2018) - Brooke, Benjamin S; Slager, Stacey L; Swords, Douglas S; Weir, Charlene R
Abstract: Care coordination for patients with chronic disease commonly involves multiple transitions between primary care and surgical providers. These transitions often cross healthcare settings, providers, and information systems. We performed a cross-sectional qualitative study to gain a better understanding of the factors that influence how patients and caregivers perceive care coordination during transitions of surgical care. Eight focus groups were conducted among individuals from three different U.S. states who had experienced an episode of surgical care within the past year. We included patients who had undergone major surgery for a chronic condition, as well as caregivers. We used Atlas.ti qualitative software and engaged in an iterative process of thematic analysis of focus group transcripts. After five-rounds of review, five main themes emerged that define chronic care coordination for surgical patients and caregivers: (a) Care coordination is embedded in the unwritten social con tract patients share with their surgical providers; (b) Patients expect all surgical and nonsurgical healthcare providers to be "on the same page"; (c) Patients are frightened and vulnerable during surgical care transitions; (d) Patients need to have accurate expectations of the processes associated with care coordination; and (e) Care coordination relies upon establishing patient trust with their surgical team and needs to be continually reaffirmed. Surgical patients and caregivers expect care coordination processes to involve informatics infrastructure, patient education, and information exchange between providers. Unfortunately, these aspects of care coordination are often lacking during transitions. These findings have implications for designing patient-centered interventions to improve coordination of chronic care. Abstract : Surgical patients and their caregivers feel vulnerable during care transitions before, during, and after surgery, and require extra efforts by the healthcare team to establish trust, define expectations of care, and support effective care coordination.